Idejnopolitični profil Antona Korošca v tridesetih letih 20. stoletja - Batič, Matic (Studia Historica Slovenica, 2023)
The treatise discusses the political orientation of Dr Anton Korošec in the 1930s, i.e. in the final period of his political career. The authors find that an important source for studying this theme is the close relations Korošec developed with Stražarji (Guards), a group of Catholic students at the University of Ljubljana who, under the spiritual guidance of Lambert Ehrlich, advocated integrationist and corporatist views. Thus, the treatise analyses the ideological profile of Stražarji by analysing their periodical, Straža v viharju (Guard in the Storm), emphasising that political concepts need to be adequately contextualised to be understood correctly as the same concepts can have different meanings. Based on this, the authors find that it is sensible to explore Stražarji as an example of the conservative right or as representatives of Catholic anti-modernism. This point of view outlines many differences from fascism, an ideology of political modernism.
Keywords: Academic Club Straža; Akademski klub Straža; fascism; fašizem; Korošec, Anton; political antimodernism; political thought; politična misel; politični antimodernizem; slovenski politiki